"I love the Queen": Positioning in young British Muslim discourse. (December 2017) - Pihlaja, Stephen; Thompson, Naomi
Abstract: Stereotyping of Muslims in media and political narratives can have tangible effects on the day-to-day lives of young people. Using data from focus groups with 19 university students in London and Birmingham, UK and focusing on extracts from the data in which participants tell stories about their own experiences, this article explores how young British Muslims position themselves in response to negative media narratives about Muslims, particularly after terrorist attacks. The analysis shows that the media was seen as a driving force behind negative stereotypes about Muslims, and this resulted in pressure on Muslims to present themselves in non-threatening and welcoming ways to others, despite being subjected to covert and overt discrimination which participants felt in various contexts. Participants suggested that discrimination could be difficult to identify and quantify, and even when discrimination was overt, it could be illogical and incoherent, and therefore difficult to respond to in a meaningful way.